THE NEED OF ENGLISH FOR INDONESIAN YOUNG LEARNERS; STUDENT’S PERSPECTIVE AND LEARNING DIFFICULTIES - Eni Faridah (UICELL, 2021)
The discussions about English education at an early age have led to different perspectives. Many studies have shown that "younger is better" at learning English. However, it is no longer acceptable claiming that it is better to start early or that adult learners are better than young people in most of cases. In addition, there are many studies in which the analysis concern on the teacher’s perspective to look at the challenges of teaching English to young learners. Therefore, this study aims to reveal how students perceive English language in general. This study carried out a narrative research method in which the primary data was collected from the reflections of the students' memoranda and supported by a semi-structured interview. Meanwhile, the sampling was done through purposive sampling technique. The research results are analyzed thematically which include several points: (A) Student's Perspective, (B) Student’s Difficulties in Learning English, and (C) Student's desire to have an Ideal English teacher. Based on the discussion of the results, this study also proposes several approaches in teaching English for young learners. Thus, it provides a complete picture of TEYL in Indonesian context and is expected to give English teachers an idea of the importance of considering aspects related to the challenges and difficulties of young learners from a learning perspective. Keyword: TEYL, student’s perspective, teaching challenges, learning difficulties